2016
DOI: 10.1042/cs20160480
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic control of exercise training-induced cardiac hypertrophy by miR-208

Abstract: Aerobic exercise-induced cardiac hypertrophy (CH) is a physiological response involving accurate orchestration of gene and protein expression of contractile and metabolic components. The microRNAs: , and are each encoded by a myosin gene and thus are also known as 'MyomiRs', regulating several mRNA targets that in turn regulate CH and metabolic pathways. To understand the role of myomiRs in the fine-tuning of cardiac myosin heavy chain (MHC) isoform expression by exercise training-induced physiological hypertr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 40 publications
3
37
0
3
Order By: Relevance
“…Consistent with this, cardiac miR‐208b levels are known to be downregulated following endurance exercise (Soci et al . ). However, it is unlikely miR‐208b is responsible for the sustained increase in cardiomyocyte number since its current known function in the heart is the regulation of myosin heavy chain expression (Soci et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Consistent with this, cardiac miR‐208b levels are known to be downregulated following endurance exercise (Soci et al . ). However, it is unlikely miR‐208b is responsible for the sustained increase in cardiomyocyte number since its current known function in the heart is the regulation of myosin heavy chain expression (Soci et al .…”
Section: Discussionmentioning
confidence: 97%
“…However, it is unlikely miR‐208b is responsible for the sustained increase in cardiomyocyte number since its current known function in the heart is the regulation of myosin heavy chain expression (Soci et al . ; Zhou et al . ) and myh6 mRNA levels were unaltered in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that there were no significant changes of blood lipids (Total cholesterol, LDL cholesterol, Triglyceride), renal function (serum creatinine), arterial stiffness (BaPWV) and plasma glucose (HbA1c) between non-sarcopenia and sarcopenia group, while blood lipids marker HDL cholesterol of sarcopenia group was significantly higher than that of nonsarcopenia group. We determined the expression of angiogenesis-related miRNAs (miR-20a, miR-126, miR-210, miR-221, miR-222, and miR-328) (Dews et al, 2006;Poliseno et al, 2006;Kuehbacher et al, 2007;Fasanaro et al, 2008;Soeki et al, 2016), inflammationrelated miRNAs (miR-21, miR-146a, and miR-155) (Taganov et al, 2006;Urbich et al, 2008;Wang et al, 2017) and cardiac or muscle-specific/enriched miRNAs (miR-1, miR-133a, miR-133b, miR-208b, miR-486, and miR-499) (Chen et al, 2006;Alexander et al, 2014;Soci et al, 2016). Firstly, the results of small-sample screening experiment showed that plasma miR-208b, miR-499, miR-155, miR-222, miR-328, and miR-210 levels were significantly down-regulated in sarcopenia group compared to those who non-sarcopenia.…”
Section: Subject Characteristicsmentioning
confidence: 99%
“…Differently from which is found in pathological CH [61], high volume ET decreases the expression of cardiac miRNA-208a in healthy, induces the upregulation of targets such as THRAP-1, Purβ, and Sox6, and improves the balance between βMHC and αMHC gene expression [2,84]. In addition, in recent study, Fernandes et al [85] showed that aerobic ET prevents weight gain and pathological CH in obese Zucker rats, via increase of cardiac MED13 by regulation of miRNA-208.…”
Section: Mirnas Regulation By Exercise Training In Cardiac Remodelingmentioning
confidence: 99%